Management of Posterior Cervical Epidural Abscess Complicated by Non-Communicating Tetra-Ventricular Hydrocephalus: A Case Report and Review of the Literature - Boris, Gbassara Koulagna; Djoubairou, Ben Ousmanou; Figuim, Bello; Poulenc, Njofang Teto; Mathieu, Motah; Vdp, Djientcheu (WFNS Journal, 2025)
Background Spinal epidural abscess (SEA) is an uncommon condition, especially in children. Its occurrence in the cervical spine, particularly without significant osseous involvement, is exceedingly rare. We report a case of non-communicating tetra-ventricular hydrocephalus associated with a posterior cervical epidural abscess. The condition was managed with surgical drainage, specific antibiotics, and ventriculoperitoneal shunting.Case Description A 15-year-old female presented with a history of posterior cervical abscess drainage. Bacteriological findings revealed two microorganisms (Staphylococcus epidermidis and tuberculosis) despite initial improvement following surgical intervention and antibiotic therapy, the patient experienced a recurrence of symptoms, including fever and deterioration in consciousness. Imaging revealed a tetra ventricular hydrocephalus, prompting urgent ventriculoperitoneal shunt placement. Subsequent treatment with anti-tuberculous therapy and vancomycin led to favorable outcomes.Conclusion SEA poses diagnostic and management challenges, particularly in resource-limited settings. Prompt recognition, appropriate antimicrobial therapy, and surgical intervention are crucial for favorable outcomes. Consideration of tuberculous and S. epidermidis etiology, even in atypical presentations, is essential.
Keywords: spinal epidural abscess; hydrocephalus; ventriculoperitoneal shunt; cervical spine; tuberculous etiology; Staphylococcus epidermidis